2021
DOI: 10.1172/jci144016
|View full text |Cite
|
Sign up to set email alerts
|

TNFR2/14-3-3ε signaling complex instructs macrophage plasticity in inflammation and autoimmunity

Abstract: TNFR1 and TNFR2 have received prominent attention because of their dominance in the pathogenesis of inflammation and autoimmunity. TNFR1 has been extensively studied and primarily mediates inflammation. TNFR2 remains far less studied, although emerging evidence demonstrates that TNFR2 plays an anti-inflammatory and immunoregulatory role in various conditions and diseases. Herein, we report that TNFR2 regulates macrophage polarization, a highly dynamic process controlled by largely unidentified intracellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 79 publications
(98 reference statements)
0
33
0
Order By: Relevance
“…Therefore, a pathway common to the IL1R and TNF receptors is activated to block M2 gene expression downstream of STAT6. Recent results showed the type 2 TNF receptor is involved in the control of M2 gene expression and indeed, loss of TNFR2 caused altered Arg1 and Mgl2 expression in M2 polarization conditions ( Fu et al, 2021 ). However, when we used BMDMs lacking the TNFR1, TNF-mediated suppression of Retnla was completely lost ( Fig 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a pathway common to the IL1R and TNF receptors is activated to block M2 gene expression downstream of STAT6. Recent results showed the type 2 TNF receptor is involved in the control of M2 gene expression and indeed, loss of TNFR2 caused altered Arg1 and Mgl2 expression in M2 polarization conditions ( Fu et al, 2021 ). However, when we used BMDMs lacking the TNFR1, TNF-mediated suppression of Retnla was completely lost ( Fig 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to microglia, astrocytes are the largest and most abundant glial cells in the CNS, contributing to the maintenance of its health and function, which have also been implicated in the onset and progression of several neurodegenerative diseases [ 55 , 56 ]. Recently, we reported that PGRN mediated the macrophage polarization and switch [ 57 ], suggesting the critical role of PGRN in macrophage-mediated inflammation. In this study, we revealed that the brains of PGRN-deficient mice displayed enhanced activation of microglia and astrocytes compared with age-matched WT mice, further indicating the critical role of PGRN in regulating systematic inflammation in CNS.…”
Section: Discussionmentioning
confidence: 99%
“…tmTNFα+ M2 macrophages were more potent in inducing Treg differentiation and proliferation ( 48 ). 14-3-3ϵ was essential for TNFR2 signaling-mediated regulation of macrophage polarization and switch ( 76 ).…”
Section: Non-malignant Cells Involved In Targeting Tnfr2 In Tmementioning
confidence: 99%